Determinação da Soropositividade para Leptospirose em Ovinos. - Sousa, Sebastiana Adriana Pereira (Universidade Federal do Tocantins, 2023)
Leptospirosis is a disease widely distributed that often affects the productivity of small ruminants. This infection is caused by bacteria belonging to the genus Leptospira spp. and characterized to be a major cause of reproductive failure and death in animal production. In this context, sheep can be often affected, seen that comprise the class of susceptible animals in a breeding system. Considering the importance of the productive chain of the sheep and the absence of seroepidemiological data on ovine leptospirosis in Tocantins state, the present study aimed to determine the seropositivity for leptospirosis in sheep flocks of 11 farms registered in association of sheep breeders of the city of Colinas, Tocantins, Brazil. The results for 431 serum samples collected were obtained by the Microscopic Agglutination Test (MAT) and each sample tested for a battery of 24 serovars. Descriptive statistical analysis was used to calculate the total frequency and to frequency for each serovar and to compare the results versus the animal categories as a risk factor or protective factor Fisher's exact test, with P < 0.05, and Odds Ratio with a confidence interval of 95 % were calculated. Each of the farms surveyed had at least one positive animal. Positivity was observed for 16 serovars, of which Autumnalis, Hardjo bovis, Wolffi, Patoc and Hebdomadis were the most frequent. So as prophylaxis and for the maintenance of herd health, we recommend the use of polyvalent vaccines for the most frequent serovars accompanied by basic measures of health management and isolation and treatment of sick animals.